Encryption, authentication and copyright protection techniques for digital images - Fawad, Ahmed (2011)
For the past several years, a lot of research work has been underway to devise security techniques to protect multimedia data like audio, image and video. A question that arises is why new techniques for multimedia security are required when the field of cryptography is already well matured? There are several reasons that actually impede the direct use of cryptographic techniques for solving multimedia security problems. For example, an image encrypted using the AES algorithm cannot be correctly decrypted if it undergoes JPEG lossy compression. In multimedia scenarios, content preserving operations like lossy compression, enhancement, transcoding, etc are very common. Applying standard cryptographic techniques directly to the entire multimedia data stream will have problems because a single bit error in the transmitted data stream will cause errors in the data recovery stage. Hence there is a need to devise security algorithms that are focused specifically towards multimedia environment keeping in view its very intrinsic nature.